The feeding of children from one to five years / issued by the Ministry of Health (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages MH THE FEEDING OF CHILDREN FROM ONE TO FIVE YEARS PRICE 4D NET ISSUED BY THE MINISTRY OF HEALTH PUBLISHED BY HIS MAJESTY’S STATIONERY OFFICE 127/NU/5/5/1/28